Kombinasi Rebusan Daun Salam dan Kemangi dalam Menurunkan Kadar Asam Urat Mus musculus - Fahlia Nirmala; Kholifatuz Zumaroh; Novia Afriani Donatomo; Khoirul Ngibad (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Indonesia is one of the world’s largest of biodiversity. Especially bay leaves (Syzygium polyanthum) and basil leaves (Ocimum basilicum). These plants can be used to reduce blood uric acid. This study aimed to determine the optimum dose that could reduce uric acid levels by providing a combination of decoction of basil leaves and bay leaves and to knew the phytochemical compounds that could reduce uric acid levels in basil leaves and bay leaves. The antihiperuricemia activity of boiled bay leaves and basil leaves was tested on male sex mice (Mus musculus) Balb / C strain, aged 8-10 weeks to reveal the effectiveness of bay leaves and basil leaves as blood uric acid-lowering. The dosage of decoction used is 1.5 glasses, 1 glass, and 0.5 glass from the shrinking of the cooking water which was originally 2 glasses. Tests were carried out on mice that experienced hyperuricemia induced by potassium oxonate 250 mg / kg BW or 5 mg / 20 g BB in mice intraperitoneally and mixed chicken liver, sprouts and melinjo. Measuring the level of urate is done using the POCT (Point Of Care Tasting) method. The results showed that combination of boiled bay leaves and basil leaves could reduce blood uric acid levels in mice around 0.5 - 1.0 mg / dl. The activity was effective in both doses, 0.5 glass and 1.5 glasses, but to get a significant decrease in uric acid levels this cooking water had to be consumed regularly and for a longer time.